Effects of a dicalcium and tetracalcium phosphate-based desensitizer on in vitro dentin permeability - Zhou, Jianfeng; Chiba, Ayaka; Scheffel, Debora L. S. [UNESP]; Hebling, Josimeri [UNESP]; Agee, Kelli; Niu, Li-Na; Tay, Franklin R.; Pashley, David H. (Public Library of Science (PLoS), 2016)
The present study evaluated the effectiveness of a dicalcium and tetracalcium phosphatebased desensitizer in reducing dentin permeability in vitro. Dentin fluid flow was measured before and after treatment of dentin with patent dentinal tubules using 1 or 3 applications of the dicalcium and tetracalcium phosphate containing agent TeethmateTM (TM) and comparing the results with two sodium fluoride varnishes VellaTM (VLA) and VanishTM (VAN), after storage in artificial saliva for 24 h, 48 h and 7 days. Significant differences were observed among the 4 methods employed for reducing dentin permeability (p < 0.001) and the 3 posttreatment times (p < 0.001). VLA and VAN never achieved 50% permeability reductions consistently in any of the 3 time periods. Only the calcium phosphate-based desensitizer applied for 3 times consistently reduced dentin permeability by 50% after 24 h. When applied once, the permeability reduction of TM increased progressively over the 3 time periods. After 7 days, only one and three applications of the calcium phosphate-based desensitizer consistently reduced dentin permeability by more than 50%. Permeability reductions corresponded well with scanning electron microscopy examination of dentinal tubule orifice occlusion in dentin specimens treated with the agents. Overall, the dicalcium and tetracalcium phosphate-based desensitizer is effective in reducing dentin permeability via a tubule occlusion mechanism. The ability of the agent to reduce dentin permeability renders it to be potentially useful as a clinical dentin desensitizing agent, which has to be confirmed in future clinical studies. By contrast, the two sodium fluoride varnishes are not effective in dentin permeability reduction and should be considered as topical fluoride delivering agents rather than tubular orifice-blocking agents.